Estudo da degradação forçada de Gliclazida sob a forma de comprimidos e validação de método analítico indicativo de estabilidade empregando HPLC-DAD - Coradi Junjior, Olair (2023)
To market a medicine, it must undergo quality tests to assess its safety and efficiency. Therefore, analytical analyzes are carried out to evaluate quality, the main ones being: identification, assay, degradation products, disintegration, friability, dissolution, uniformity of content and microbiological analysis. Therefore, in the study an analytical method was developed by HPLC- DAD, quantifying the content and impurities in the same chromatographic run. After development tests, chromatographic parameters were defined for validation. The chromatographic column used is a Waters XbridgeTM C18 (250 x 4.6 mm, 3.5 µm) at a temperature of 30 ºC. The system has an elution gradient, with the mixture of 0.1% Triethylamine solution in purified water with the pH adjusted to 3.8 with phosphoric acid and Acetonitrile. The mobile phase flow rate was 1.0 mL min-1, with detection at 235 nm, in an analytical run of 50 minutes. Validation of the analytical method followed RDC 166/2017 of ANVISA, harmonized with ICH. In the statistical evaluation of Linearity, both the dosing method and the degradation product method were found to be linear. The dosing method was accurate, with a DPR of 0.6%. Likewise for non-specific impurities, where a DPR of 2% was observed for the low and high level, 3% for the medium level. Impurity G, for the low level the DPR was 3%, at the medium level 6% and at the high level 4%. As for Impurity A, at the low level the DPR was 4%, for the medium and high level it was 3%. In Accuracy, the dosing method showed an average recovery of 100% for the low and medium level, for the high level it was 99%. For non-specific impurities, the average recovery was 95% for the low level, 100% for the medium level and 101% for the high level. Impurity G obtained 102% for the low level, 96% for the medium level and 94% for the high level of medium recovery. Likewise, Impurity A obtained 101% for the low level, 97% for the medium level and 96% for the high level. Therefore, the methods proved to be precise, exact and linear in the working range and for impurities, the limit of quantification was adequate. In Selectivity, the acid hydrolysis stress condition resulted in a decay of close to 10% in 2 hours of exposure. Oxidation by metal ions caused a decay of approximately 15% after 6 hours of exposure. The other stress conditions of basic hydrolysis and peroxide oxidation showed decay after 10 days of exposure and for the physical stress conditions (thermal, humid and actinic) there was no degradation in 10 days.